Case study research in practice - Simons, Helen (Thousand Oaks : SAGE Publications, 2009)
Drawing on her extensive experience in teaching and using case study research, Helen Simons provides a practical guide that addresses common misconceptions and the questions often raised by students approaching case study research for the first time.
1. Evolution and concept of case study research -- 2. Planning, designing, gaining access -- 3. Listen, look, document : methods in case study research -- 4. Who are they? Studying others -- 5. Who are we? Studying our 'self' -- 6. Whose data are they? Ethics in case study research mid-term letter -- 7. Begin at the beginning : analysis and interpretation -- 8. From data to story : examples in practice -- 9. Start at any point : reporting and writing -- 10. Dispelling myths in case study research
Includes bibliographical references (p. [173] - 181) and index
Keywords: Data Collection -- methods; Research -- methods; Social sciences -- Research -- Methodology